HISTOMORPHOMETRY OF AGRANULOCYTE WHITE BLOOD CELLS OF BALI CATTLE IN NUSA PENIDA - Adinugroho, M. Oenas; Suwiti, Ni Ketut; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2019)
This study aims to determine about the histology structure and the morphometry white blood cells agranulocytes (lymphocytes and monocytes) of Bali cattle in Nusa Penida. A sample of blood from 50 female calves, had been taken through a jugular vein. The blood samples were fixed and colored by using Giemza staining method. The morphometry measurement was performed with was done under Axio Zeiss Imager 2 microscope with 1000x magnification. The results of the measurements were analyzed descriptively quantitatively, while the histology description was analyzed by qualitative descriptive. The results showed average mean lymphocyte diameter (9.22 ± 0.73µm) was smaller than monocytes (12.48 ± 1.73 µm). The existence of the lymphocyte and monocytes histologic structure difference which are found in the nucleus. The lymphocyte nucleus was round and filled the cytoplasm, whereas the monocyte nucleus formed a curve on one or two sides, thus, it did not fill the cytoplasm.